INITIAL PERIODONTAL THERAPY: NON-SURGICAL THERAPY - Soares, Kaio Henrique; Martins, Olga Beatriz Lopes; Leite, Mariana Botelho; Alves, Sâmia Francy Ferreira; Lopes, Maria Rita Lima; Santos, Jefferson Aguiar; Paulino, Gabriela Leite; Soares, Célio Leone Ferreira (Seven Editora, 2026)
Initial periodontal therapy, also known as non-surgical therapy, forms the fundamental basis of periodontal disease treatment, with the main objective of controlling bacterial infection and periodontal inflammation through the removal of biofilm and dental calculus. This chapter describes in detail the steps of periodontal treatment, including anamnesis, clinical and radiographic examination, patient motivation, oral hygiene instruction, scaling and root planing, as well as the complementary use of antimicrobial chemical agents. The importance of identifying and correcting local plaque-retentive factors is also highlighted, as well as periodontal reassessment after initial therapy to determine the need for maintenance or surgical intervention. An integrated and individualized approach is emphasized as essential for stabilizing the disease and maintaining long-term periodontal health.